The Role of the Traffic Education Community Unit in Minimizing Traffic Violations in Cirebon Police Department - Regina Andrilla Setiawan (Akademi Kepolisian Republik Indonesia, 2021)
Traffic violations in Cirebon Police are increasing every year, so the efforts of the Sat Lantas Cirebon Police are to provide Dikmas Lantas to the community as a form of prevention. The purpose of this thesis writing is to explain the role of the Cirebon Police Traffic Council in minimizing traffic violations and explain the factors that influence the implementation of the Cirebon Police Traffic Council. Theories and concepts used by the author are Role Theory by Biddle and Thomas, Management Theory by G.R. Terry, Concept of traffic violations, Dikmas Lantas concept, National Police Chief Implementation Guidelines Pol .: Juklak/5/V/2003 dated May 29, 2003 concerning the instructions for the implementation of Community Education (Dikmas Lantas) and the Kamseltibcar Lantas Concept. The approach used is a qualitative approach. Data collection techniques are by interviewing, observing and studying documents. The results obtained by the author in this study are the role of Dikmas Lantas in minimizing traffic violations in Cirebon Police, which are applied with role theory, management theory and operational guidelines No. Pol .: Juklak/5/V/2003 concerning the Implementation of Dikmas Lantas. The results of the implementation of the Lantas DASAS have not been as expected because the number of traffic violations every year is still increasing because of personnel, budgetary factors and the DASAS Lantas has not been conveyed to all levels of Cirebon society. The author suggests that there is a need to improve the ability of personnel, especially in the units in charge, increase the budget and members and activities that are more varied and conveyed to all elements of society.